Design of Major Components of Green Urea Production Plant - Poudel, Toyanath; Bhandari, Sabin; Thapa, Yuvraj; Nepal, Samundra (International Journal on Engineering Technology, 2024)
Green urea refers to urea produced using renewable energy sources such as municipal solid wastes (MSW) to create a more sustainable and eco-friendly approach to waste management and urea production. As the economy, population, and living standards proliferate swiftly, municipal solid waste has become a significant challenge, particularly in developing countries such as Nepal. This project aims to size the major components of a green urea plant that uses decomposable and combustible waste as feedstock. 15 CSTR digesters with a volume of 53323.2 m3 produced 41473.2 m3 of biogas to convert 740.6 Tons Per Day (TPD) of decomposable waste and 220.06 TPD of combustible waste into 574.4 TPD of green urea. A circulating fluidized bed gasifier, a Proton Exchange Membrane (PEM) electrolyzer, and an air separation unit using the cryogenic process were also selected. The study also involved picking a tubular steam methane reformer as the primary and an auto-thermal steam methane reformer as the secondary steam methane reformer. The shift reaction was carried out using a catalytic water gas shift reactor, and a three-bed type ammonia reactor was chosen for the Haber Bosch process. Finally, the Snamprogetti process was selected for urea synthesis. In addition, the study involves the preparation of a 2D system layout to understand the process flow and a 3D solid works drawing to visualize the plant design. The financial analysis of the green urea plant includes the calculation of CAPEX and OPEX, and it is found that total capital investment is 431.45 M$ and operating expenses are 102.2M$/year. Gasification, steam methane reformer, Air separation unit, ammonia synthesis, urea synthesis, electrolyzer, water gas shift reactor, and anaerobic digestion plant consist 7.15%, 13.55%, 3.32%, 16.13%, 26.12%, 13.37%, 13.43% and 6.93% of total capital investment respectively and 14.62%, 1.61%, 7.78%, 19.73%, 5.71%, 32.6%, 12.9% and 14.62% of total operating costs per year.